The humour of Holland - Dircks, W. H. (Will H.); Hardy, Dudley, 1867-1922; Werner, Alice, 1859-1935 (Salt Lake City, UT : Project Gutenberg, 2021)
"The Humour of Holland" edited by W. H. Dircks, Alice Werner, and illustrated by Dudley Hardy is a collection of humorous writings that captures the essence of Dutch humor, likely written in the late 19th century. This compilation includes a variety of pieces, each showcasing the unique comedic traits of the Netherlands, offering insight into the social and cultural life of Dutch society through laughter and satire. The contributors, including Frederick Van Eeden and Multatuli, engage with themes of everyday life, politics, and human follies. The opening of the collection introduces readers to a play titled "The King's Dream," featuring King Bilbonzo and his court as they navigate a bizarre and comedic dream involving a monstrous sea creature. The scene sets the tone for the humor that follows, highlighting the absurdity of royal life and the folly of courtly advisers in a lighthearted manner. Subsequent pieces, such as "The Dominie" and "My Hero," delve into the quirks of rural life and childhood aspirations, blending satire with heartfelt moments. Overall, the beginning captures a range of voices and styles, promising an entertaining exploration of Dutch humor that resonates across situations and characters. (This is an automatically generated summary.)
Release date is 2021-03-08
MFR, Richard Tonsing, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Dutch wit and humor